INTERAKTIVITAS PENGUNAAN MEDIA SOSIAL INSTAGRAM KAHE.ID DALAM MENINGKATKAN CUSTOMER ENGAGEMENT - Putri Komalasari; Johantan Alfando W.S (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Currently, marketing a product can be done anywhere and anytime when needed, with the existence of increasingly sophisticated technology, product marketing can be traded or traded via the internet. Instagram is one of them which is a type of new media that can be used as a means or tool in the communication process. In the context of marketing on social media, especially Instagram, the level of customer engagement is the main indicator for business people and advertisers. This research aims to describe and analyse how the interactivity of using kahe.id Instagram social media in increasing customer engagement. The theory used in supporting this research is New Media. This research uses descriptive qualitative research methods. The type of data presented is observation and interviews using primary data through key informant and informant data sources, secondary data through document sources, e-journals, books, articles and documentation. The analysis technique used is qualitative data analysis interactive model developed by Miles & Huberman. Based on the results of the study, it can be seen that Kahe.id only applies several models from 3 interactivity concepts. Through the user to user element Kahe.id applies three models namely monologue, feedback and responsive dialogue and does not apply the mutual discourse model. Then on the user to system element, Kahe.id only applies one model, namely adaptive interaction and does not apply the computer-based interaction model. Then in the user to document element, Kahe.id only applies the content on demand model. While packaged content & content exchange are not applied. Some of these models are used to maintain Kahe.id customer engagement.